2012
DOI: 10.1159/000331899
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor of Activated T Cells 5 Deficiency Increases the Severity of Neuronal Cell Death in Ischemic Injury

Abstract: Nuclear factor of activated T cells 5 (NFAT5) has been implicated in regulating several genes that are thought to be neuroprotective in ischemic injury. Because of the embryonic lethality of NFAT5 knockout (NFAT5–/–) mice, the heterozygous (NFAT5+/–) mice were used to study the in vivo role of NFAT5 in hypoxia/ischemia (H/I) condition. The NFAT5+/– mice exhibited more severe neurological deficits, larger infarct area and edema formation associated with increased aquaporin 4 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…For example, TonEBP reportedly contributes to the pathogenesis of diabetic complications, especially diabetic nephropathy [13] . Furthermore, TonEBP is not only essential for neuronal adaptation to hypertonic conditions but is also vital for regulating the transcription of genes to protect neurons against ischemiainduced neuronal death [36] . A recent manuscript identified TonEBP as an essential transcription factor for the regulation of osmotic homeostasis and showed that TonEBP is upregulated in the hyperglycemic diabetesdamaged retina [13] .…”
Section: Discussionmentioning
confidence: 99%
“…For example, TonEBP reportedly contributes to the pathogenesis of diabetic complications, especially diabetic nephropathy [13] . Furthermore, TonEBP is not only essential for neuronal adaptation to hypertonic conditions but is also vital for regulating the transcription of genes to protect neurons against ischemiainduced neuronal death [36] . A recent manuscript identified TonEBP as an essential transcription factor for the regulation of osmotic homeostasis and showed that TonEBP is upregulated in the hyperglycemic diabetesdamaged retina [13] .…”
Section: Discussionmentioning
confidence: 99%
“…NFAT5 also had various roles in the CNS, such as regulating the expression of AQP4 in astrocytes [13], protecting neurons and astrocytes against ischemic damage [14, 33], and participating in neuroinflammation [16]. …”
Section: The Function Of Nfat5mentioning
confidence: 99%
“…2), although its function is not well understood because of insufficient studies in this area. Besides its classic role in osmotic protection, NFAT5 attenuates the severity of neuronal cell death, infarct area, and edema formation in ischemic injury [14, 15]. It also influences dopaminergic neurotransmission [59] and the action of potential firing of superior cervical ganglion neurons by mediating SMIT1 and KCNQ2/3 [60].…”
Section: The Function Of Nfat5mentioning
confidence: 99%
See 2 more Smart Citations